Structural and Optical properties of Polymers(PVA / PVP ) doped with V2O5 composites films - S. Ahmed, Ghuzlan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Study the effect of doping V2O5 on polymers poly vinyl alcohol ( PVA), poly vinyl pyrrolidone (PVP) on the optical and structural properties for film prepared by using Casting method at thickness( 300Â±20)nm ,All the materials dissolved in distilled water  by magnetic mixer for one hour .The optical parameters measured by using UV-VIS spectrometer ,and the structural parameters measured by X-ray diffraction .when measured the energy gap found that the value was decreases from 4.6 eV to 2.98 eV with doping .The refractive index ,extinction coefficient ,absorption coefficient ,real and imaginary dielectric constants of (PVA/PVP) are increasing with doping by V2O5 and with increase the ratio of doping .